Elucidating the role of N-acetylglucosamine in Group A Carbohydrate for the development of an effective glycoconjugate vaccine against Group A Streptococcus. (1st July 2023) - Pitirollo, Olimpia; Di Benedetto, Roberta; Henriques, Pedro; Gasperini, Gianmarco; Mancini, Francesca; Carducci, Martina; Massai, Luisa; Rossi, Omar; Volbeda, Anne Geert; Codée, Jeroen D.C.; Berlanda Scorza, Francesco; Moriel, Danilo Gomes; et al.
Abstract: Group A Carbohydrate (GAC), conjugated to an appropriate carrier protein, has been proposed as an attractive vaccine candidate against Group A Streptococcus infections. Native GAC consists of a polyrhamnose (polyRha) backbone with N -acetylglucosamine (GlcNAc) at every second rhamnose residue. Both native GAC and the polyRha backbone have been proposed as vaccine components. Here, chemical synthesis and glycoengineering were used to generate a panel of different length GAC and polyrhamnose fragments. Biochemical analyses were performed confirming that the epitope motif of GAC is composed of GlcNAc in the context of the polyrhamnose backbone. Conjugates from GAC isolated and purified from a bacterial strain and polyRha genetically expressed in E. coli and with similar molecular size to GAC were compared in different animal models. The GAC conjugate elicited higher anti-GAC IgG levels with stronger binding capacity to Group A Streptococcus strains than the polyRha one, both in mice and in rabbits. This work contributes to the development of a vaccine against Group A Streptococcus suggesting GAC as preferable saccharide antigen to include in the vaccine. Graphical abstract: Unlabelled Image